ANALISIS MODAL SOSIAL KELOMPOK USAHA AGROINDUSTRI KERIPIK NENAS DI DESA KUALU NENAS KECAMATAN TAMBANG KABUPATEN KAMPAR - Tia Fitri Jayanti; Roza Yulida; Kausar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aims to determine the social capital in the bussiness group of pineapple chips agro-industry. This research uses a survey method with respondents consist of 12 craftsman pineapple chips. Data collection method in this research is primary data and secondary data. To determine the social capital in this research using a quantitative method using a questionnaire in the form of Likert Scale. Social capital in this research in view of the three elements of the network, social norms and trush. Value of the network of their way association, social norms in the value of the formation of attitudes and regulatory compliance, value of trush from the trush they have to offer a contribution to the bussiness group of pineapple chips agro-industry. Social capital in the of pineapple chips scored 3.24 are categorized high enough. Keywords: social capital, pineapple chips agro-industry, bussiness group.